Microstructure evolution and creep resistance of a Z-phase strengthened 12% Cr steel - Timhagen, Johanna (My University, 2019)
9–12% Cr steels are a family of steels, which are the backbones for today’s fossil fuel steam power plants, which provide more than 60% of electricity worldwide. By developing more creep and corrosion resistant 9–12% Cr steels, the operation temperature of 620°C could be increased to 650°C, which would reduce the environmental impact. For improved resistance to corrosion, a higher Cr content is needed. However, an increased Cr content results in formation of stable but big detrimental Z-phase precipitates. While Z-phase traditionally results in premature creep failures, a new alloy design strategy, called Z-phase strengthening, aims to make use of Z-phase particles as strengthening precipitates rather than detrimental particles. Getting a better understanding of the correlation between microstructure evolution and creep resistance in these steels, could potentially lead to a solution to the conflict between creep and corrosion resistance at 650°C. In this study, two versions of the same 12% Cr steel have been evaluated, one version is tempered at 700°C and the other at 740°C. Investigation have been done with light optical microscopy (LOM), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDX). Results from these methods were correlated with results from mechanical testing and creep testing, and together they provided a better understanding of the evolution of nano-sized particles at high temperatures. It was found that tempering with a lower temperature results in better creep properties. Mechanical properties are also improved by a lower tempering temperature, but eventually the values of hardness, tensile testing, and impact toughness for the two different versions coverage with ageing. M23C6 particles grow very slowly. Laves-phase is significantly affected by tempering temperature. A higher tempering temperature results in Z-phase particles that start to transform from MX particles after a shorter ageing time. The average particle size is smaller with a lower tempering temperature. A lower tempering temperature results in superior microstructure regarding nano-sized particles.
Keywords: Materialvetenskap; Produktion; Maskinteknik; Materialteknik; Materials Science; Production; Mechanical Engineering; Materials Engineering